Holocene temperature trends in the extratropical Northern Hemisphere based on inter‐model comparisons. (17th April 2018) - Zhang, Yurui; Renssen, Hans; Seppä, Heikki; Valdes, Paul J.
ABSTRACT: Large uncertainties exist in Holocene climate estimates, especially for the early Holocene when large‐scale reorganization occurred in the climate system. To improve our understanding of these uncertainties, we compare four Holocene simulations performed with the LOVECLIM, CCSM3, HadCM3 and FAMOUS climate models. The simulations are generally consistent for the large‐scale Northern Hemisphere extratropics, while the multi‐simulation consistencies are heterogeneous on the sub‐continental scale. Consistently simulated temperature trends are found in Greenland, northern Canada, north‐eastern and north‐western Europe, and central‐west Siberia. These Holocene temperatures show a pattern of an early Holocene warming, mid‐Holocene warmth and gradual decrease towards the pre‐industrial in winter, and the extent of early Holocene warming varies spatially, with 9 °C warming in northern Canada compared with 3 °C warming in central‐west Siberia. In contrast, mismatched temperatures are detected: in Alaska, the warm early Holocene winter in LOVECLIM primarily results from strongly enhanced southerly winds induced by the ice sheets; in eastern Siberia, the intense early‐Holocene summer warmth anomaly in CCSM3 is caused by large negative albedo anomalies due to overestimated snow cover at 0 ka; in the Arctic, cool winter conditons in FAMOUS can be attributed to extensive sea ice coverage probably due to simplified sea ice representations. Thus, the Holocene temperature trends in these regions remain inconclusive.